Analyzing the Effects of Trade Wars on Global Supply Chains and Economic Growth - Sarinah, Syifah; Fajriani, Yulida Nur; Basri, Basri (Scieclouds Publishing, 2023)
This study aims to analyze the effects of trade wars on global supply chains and economic growth, focusing on the economic and business disruptions caused by escalating tariffs and protectionist policies. Using quantitative data from official sources such as the World Bank, IMF, and WTO, the study examines key metrics including trade volumes, GDP growth, tariff rates, and supply chain performance between 2016 and 2020. Methods such as descriptive statistics, difference-in-differences analysis, regression analysis, time series analysis, were employed to assess the impacts of the trade wars, particularly between major economies such as the United States and China. The results show a significant decline in trade volumes and GDP growth during the peak years of the trade wars, with both countries experiencing severe supply chain disruptions, evidenced by increased lead times and rising production costs. The findings underscore the negative economic consequences of protectionist measures, which extend beyond the countries directly involved, affecting global trade relations and supply chain resilience. The study concludes by highlighting the need for policymakers and businesses to address trade tensions through international cooperation, enhanced supply chain strategies, and sustainable economic development policies.